АНАЛИЗ АКАДЕМИЧЕСКОГО ЭССЕ - Герок-Ержанова, О.В.; Лопатина, О.В. (My University, 2018)
When writing an academic assignment, good writers do not express themselves perfectly on the first try, but they do work hard at revising their initial efforts. Revision should not be confused with proofreading or editing, the final stage of the writing process, where the writer carefully inspects your word choice, spelling, grammar, and punctuation. Revision is much more drastic, often involving an upheaval of the draft as the writer changes its content and organization in order to communicate more effectively.
REVISION OF THE ACADEMIC ESSAY
Keywords: быстрый подход; акроним FACT; восстанавливать; поток идей; уточнить связь; исправления; стилистически несовершенный; тезисное утверждение; многословие; схватить; передавать; неточный; чрезмерно сложный